A review of methods to study resilience of complex engineering and engineered systems - Naghshbandi, S. Neda; Varga, Liz; Purvis, Alan; McWilliam, Richard; Minisci, Edmondo; Vasile, Massimiliano; Troffaes, Matthias; Sedighi, Tabassom; Guo, Weisi; Manley, Ed; Jones, David H. (IEEE, 2020)
Uncertainty and interconnectedness in complex engineering and engineered systems such as power-grids and telecommunication networks are sources of vulnerability compromising the resilience of these systems. Conditions of uncertainty and interconnectedness change over time and depend on emerging socio-technical contexts, thus conventional methods which can conduct normative, descriptive and prescriptive assessment of complex engineering and engineered systems resilience are limited. This paper brings together contributions of experts in complex engineering and engineered systems who have identified six methods, three each for uncertainty and interconnectedness, which form the foundational methods for knowing complex engineering and engineered systems resilience. The paper has reviewed how these methods contribute to overcoming uncertainty or interconnectedness and how they are implemented using case studies in order to illustrate essential approaches to enhancing resilience. It is hoped that this approach will allow the subject to be quantified and best practice standards to develop.
Keywords: Resilience; reliability; robustness; interconnectedness; quantification; case studies